2021
DOI: 10.1371/journal.pone.0255149
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment of Spanish adolescents and their parents during COVID-19 lockdown: A mixed method approach

Abstract: Previous literature on the psychological impact of COVID-19 has shown a direct relationship between family conflicts and psychological distress among parents and their children during the domestic lockdown and social isolation; but there are also opportunities to enhance family bonding, encourage collective problem-solving and improve personal relationships. This study aimed to explore psychological adjustment processes of Spanish adolescents and their parents during the first month of lockdown by analyzing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Although the patients experienced threats to their mental health, in response to COVID-19 pandemic, they also achieved “stress related growth”. Social support and social responsibility are mainly two protective factors of mental health during psychological adaptation process [ 40 ]. Specifically, the social support is external factor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patients experienced threats to their mental health, in response to COVID-19 pandemic, they also achieved “stress related growth”. Social support and social responsibility are mainly two protective factors of mental health during psychological adaptation process [ 40 ]. Specifically, the social support is external factor.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies we reviewed, only Scott et al [ 12 ] found that adolescents in the United States described academic issues as their biggest challenge. Young people from other countries did mention being burdened by schoolwork and distance learning [ 14 , 16 , 17 ], yet other concerns prevailed. In some studies, school-related worries were not mentioned at all [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was carried out using Research Electronic Data Capture (REDCap) [ 18 , 19 ], which is hosted at the servers of the University for Continuing Education Krems, Austria. The survey comprised 67 items measuring well-being (WHO-5), depression (PHQ-9), anxiety (GAD-7), sleep quality (ISI), stress (PSS-10), and disordered eating (EAT-8) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. To give respondents the opportunity to report in their own words and without a predefined set of answers regarding what concerned or helped them most in the current situation, the survey contained two open-ended questions: (Question 1) What currently gives you most cause for concern?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social supports during the pandemic were found positively associated with families’ socio-emotional well-being. In a previous study with parents and adolescents, the two most important protective factors regarding psychological stress were social support and keeping busy during lockdown, while the most significant risk factors were loss of mobility and social isolation [ 43 ]. Strains on parent capacities were also found to include limited social supports, as well as psychological distress and too much unstructured time [ 28 ].…”
Section: Discussionmentioning
confidence: 99%